(untitled) (Asian Journal of Medical and Biological Research, 2015)
The present study was carried out to evaluate the effect of aquaculture-drugs and chemicals on health and production of prawn in Narail district. Data were collected through questionnaire interview, market survey and focus group discussion from June to December 2014. Six categories and 28 types of chemicals were found in the chemical shops as well as used by the farmers. Chemicals used in pond preparation, equipments disinfection, oxygen supplementation, growth promotion, antibiotics and disease treatment. Eco-solution, malachite green and melathion were used in the treatment of viral diseases having 85%, 70% and 65% recovery respectively. Potassium permanganate, oxytetracycline and renamycine had 86%, 80% and 75% recovery respectively against protozoan and bacterial diseases. Clinically prawn appeared normal greenish in control ponds, whereas, in chemical treated prawn appeared yellowish brown and grayish color. Histology of muscle of control prawn were almost normal except some vacuums, however, chemical treated prawn muscle had remarkable pathological changes like necrosis, vacuums and pyknotic cells. Prawn production was 85 kg/acre in control ponds, 150 kg/ acre in lime-urea treated ponds and 450 kg/ acre in chemical treated ponds. Asian J. Med. Biol. Res. June 2015, 1(1): 89-94